FAZL IBN AHMAD'S TEACHINGS: A COMPARATIVE ANALYSIS OF ONTOLOGICAL ISSUES (Scientific journal of the Fergana State University, 2025)
This article presents a philosophical analysis of Fazl ibn Ahmad's ideas on existence and the philosophy of space as expressed in his works “Iddatul Uqul and Umdatul Ma’qul” (The Promise of Intellects and the Foundation of Intellectually Acceptable Matters). In building the New Uzbekistan, the teachings of Rumi, particularly the ideas of Fazl ibn Ahmad, remain essential in shaping spiritually mature individuals and elevating their moral and intellectual development during these complex times. The article highlights the effective use of Fazl ibn Ahmad's treatise “Iddatul Uqul and Umdatul Ma’qul” in promoting social progress, societal welfare, and addressing human needs.